Cytological steps during spermiogenesis in the house sparrow (Passes domesticus, Linnaeus) - Goes, R. M.; Dolder, H. (Churchill Livingstone, 2002)
Spermiogenesis of the domestic sparrow was investigated with the light and electron microscopes and a step by step classification is proposed. Three cell populations corresponding to early, mid and late spermatids were easily divided according to their positions in the seminiferous epithelium. In addition to this initial separation, six steps were recognized, based on nuclear morphology and the degree of chromatin condensation, in association to their acrosomal and flagellar development. Early spermiogenesis is the period previous to chromatin condensation. The first step can be recognized by the extending flagellum and the second by the pro-acrosome development in contact with the nucleus. During the third or intermediate step, chromatin condenses and the cell becomes polarized with the pro-acrosomic vesicle and the tail occupying opposite sides of the nucleus. Late spermiogenesis, including steps IV-VI, is marked by complete chromatin condensation. The final cellular modifications lead to the formation of a spiraled spermatozoon. This shape is due to the twisting of the acrosome and nucleus, as well as the helical arrangement of mitochondria around the axoneme along most of the flagellum, making an exceptionally long middle piece. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: spermiogenesis; passerine bird; ultrastructure